A complexity perspective of a meta-organization team: The role of destabilizing and stabilizing tensions. (August 2014) - Solansky, Stephanie T; Beck, Tammy E; Travis, Deandra
Organizations face the reality of needing to work with other organizations to share resources and responsibilities in pursuit of common goals. However, there is limited research regarding the complex nature of meta-organizations. Our purpose is to identify how a meta-organization team operates. We define a meta-organization team and rely on complexity theory to explain the dynamics within the meta-organization team we observed. Based on our analysis, this team was exposed to competing tensions that forced the team into a far-from-equilibrium state and allowed the team to be effective. We propose two types of tensions on complex systems: destabilizing and stabilizing. These tensions keep a system between the boundaries of equilibrium and chaos. As a result of this study, we provide details of key findings and implications of these tensions.